INCOME ANALYSIS OF PIG BREEDING BUSINESS (Case Study at Ditha Cahya Farm, Taman Village, Abiansemal District, Badung Regency) - I M. A. A., Mahardika; Sukanata, I W.; Sumardani, N. L. G. (Jurnal Peternakan Tropika; Vol 9 No 3 (2021): Vol. 9 No. 3 Tahun 2021; September - December, 2021)
This study aims to determine the production performance, income, R/C ratio, and break-even point, of Ditha Cahya Farm's pig breeding farming. This research started from September to November 2020 at the Ditha Cahya Farm located in Taman Village, Abiansemal District, Badung Regency. This study uses primary and secondary data obtained from interviews and farmer record. Variables observed in this study include the production performance, income, R/C ratio, and break-even point, of the Ditha Cahya Farm pig breeding farming. The results of this study show that the average production of piglets is 768 heads/year from 106 sows/year. With a piglet mortality rate of 10%/period. Piglets were weaned at the age of 30 days with an average weaning weight of 7,5 kg/head. Piglets will be sold at the age of 37-40 days with an average body weight of 10-12 kg/head. Income of this farm are Rp 312.762.540,-/year with R/C ratio is 1,623. This business will reach the break even point of Break Even Point (BEP) when the piglet production of 213 head/year or when the piglet price of Rp 652.653/head, Break Even Point (BEP) sales are Rp 213.000.000,-/year. Keywords: Performance, Breeding, Income, BEP, R/C ratio